The burden of tuberculosis in Ho Chi Minh City, Vietnam: a spatial analysis of drug-susceptible and multi-drug resistant cases between 2020 and 2023 - Spies, R; Hong, HN; Trieu, PP; Lan, LK; Lan, K; Hue, NN; Huong, NTL; Thao, TLTN; Quang, NL; Anh, TDD; Vinh, TV; Dang, TMH; et al. (Centers for Disease Control and Prevention, 2024)
We characterised the spatial distribution of drug-susceptible (DS) and multi-drug resistant (MDR) tuberculosis (TB) cases in Ho Chi Minh City (HCMC), a major South-East Asian metropolis, and explored demographic and socioeconomic factors associated with local TB burden. Hot spots of DS- and MDR-TB incidence were observed in the central parts of HCMC, with substantial heterogeneity observed across wards. Positive spatial autocorrelation was observed for both DS- and MDR-TB. Ward-level TB incidence was associated with HIV prevalence (incidence rate ratio [IRR] 1.77, 95% CI 1.54-2.03) and the male proportion of the population (IRR 1.05, 95% CI 1.02-1.08). No ward-level demographic and socioeconomic indicators were associated with MDR-TB case count relative to total TB case count. Our findings may inform spatially-targeted TB control strategies and provide insights for generating hypotheses about the nature of the relationship between DS- and MDR-TB in HCMC, Vietnam and the wider South-East Asia region.